2019
DOI: 10.1017/s0007114519001867
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary patterns with depressive symptoms in Chinese postmenopausal women

Abstract: Many components in diet have regulated oxidative stress, inflammatory reaction and even balance oestrogen levels. Because these factors are closely associated with depressive symptoms in postmenopausal women, it is considered that dietary factors are able to prevent and control depressive symptoms. On the other hand, a dietary pattern that considers the correlations and synergies between foods and nutrients is expected to have a greater impact on disease risk. The aim of the present study is to evaluate whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…This is the first study investigating how the dietary patterns derived by exploratory factor analysis are related to the CA in Chinese adults. These three dietary patterns were similar to those from other TCLSIH studies ( 28 , 29 ). The results suggested that greater adherence to the sweets dietary pattern was positively related to CA in women aged 50 or older, whereas no relationships were observed between dietary patterns and CA in men.…”
Section: Discussionsupporting
confidence: 87%
“…This is the first study investigating how the dietary patterns derived by exploratory factor analysis are related to the CA in Chinese adults. These three dietary patterns were similar to those from other TCLSIH studies ( 28 , 29 ). The results suggested that greater adherence to the sweets dietary pattern was positively related to CA in women aged 50 or older, whereas no relationships were observed between dietary patterns and CA in men.…”
Section: Discussionsupporting
confidence: 87%
“…Fifty studies [ 33 82 ]provided prevalence ratios. Among them, 22 studies [ 35 , 37 , 43 , 46 48 , 52 , 57 59 , 62 , 63 , 67 , 68 , 72 , 76 – 82 ] provided odds ratios between the factors and depression among postmenopausal women. In the meta-analysis, 44 studies [ 33 – 76 ] were cross-sectional, and 6 studies [ 77 82 ] were cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, 52 reports from 50 studies were included, with eight were conducted in China [ 36 , 52 , 53 , 59 , 62 , 69 , 70 , 76 ], seven in the USA [ 33 , 34 , 46 , 75 , 77 , 79 , 82 ], seven in Korea [ 36 , 47 , 48 , 55 , 57 , 58 , 67 ], six in Poland [ 38 , 40 , 44 , 50 , 51 , 66 ], six in Iran [ 45 , 49 , 54 , 64 , 65 , 68 ], five in India [ 41 , 56 , 60 , 61 , 71 ], four in Turkey [ 35 , 37 , 63 , 73 ], two in Australia [ 39 , 78 ], two in France [ 80 , 81 ], one in Japan [ 36 ], one in Spain [ 42 ], one in Greece [ 72 ], one in Jordan [ 74 ], and one in several Mediterranean islands [ 43 ]. The measurement of depression was evaluated by a validated self-report screening instrument or diagnosed by a physician.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations